Lipids, membranes, colloids and cells: A long view - Bagatolli, Luis Alberto (2021)
This paper revisits long-standing ideas about biological membranes in the context of an equally long-standing, but hitherto largely unappreciated, perspective of the cell based on concepts derived from the physics and chemistry of colloids. Specifically, we discuss important biophysical aspects of lipid supramolecular structure to understand how the intracellular milieu may constrain lipid self-assembly. To this end we will develop four lines of thought: first, we will look at the historical development of the current view of cellular structure and physiology, considering also the plurality of approaches that influenced its formative period. Second, we will review recent basic research on the structural and dynamical properties of lipid aggregates as well as the role of phase transitions in biophysical chemistry and cell biology. Third, we will present a general overview of contemporary studies into cellular compartmentalization in the context of a very rich and mostly forgotten general theory of cell physiology called the Association-Induction Hypothesis, which was developed around the time that the current view of cells congealed into its present form. Fourth, we will examine some recent developments in cellular studies, mostly from our laboratory, that raise interesting issues about the dynamical aspects of cell structure and compartmentalization. We will conclude by suggesting what we consider are relevant questions about the nature of cellular processes as emergent phenomena.